The Influence of Organizational Reconciliation Policies and Culture on Workers Stress Perceptions - Monteiro, Rosa (2020)
Work-family reconciliation plays a crucial role in the well-being of employees, having impacts at the individual, social and organizational level. Studies concluded that poor work-life balance as one of the ten predictors of psychosocial risks at work. A family-friendly culture relates to how an organization values and allows the articulation of the various spheres of its workers’ life. We intended to determine the effect of different variables like the existence of services, the organizational culture and the managers and colleagues support, on the stress experienced. A sample of 156 employees, from five organizations in the same region of Portugal, responded to a survey contributing to the empirical results of the study. We have conducted a structural equation model to test whether the factor solution of the perception of the reconciliation capability - STRESS model demonstrated a goodness of fit to the population studied. We’ve concluded that more important than the existence of reconciliation services, the perception of a supportive organizational culture, namely by colleagues and supervisors has great influence in reconciliation capability and by that way on work stress feelings. This might explain why workers do not use all the spectrum of resources provided by organizations and states to work-life reconciliation.